A New Approach to Blending and Loading Problem of Molten Aluminum - Jianhua Li; Wei Xing (Journal of Engineering and Technological Sciences, 2014)
The  problems  of  blending  electrolyzer  and  multi-constraint optimization  of  electrolytic  aluminum  scheduling  in  the  electrolytic  aluminum production process were addressed.  Based on a mathematical model analysis, a novel  hybrid  optimization  algorithm  is  proposed  for  optimization  of  blending together  the  molten aluminum  in different  electrolytic cells. An affinity degree function  was  designed  to  represent  the  path  of  aluminum  scheduling.  The mutation  operators  were  designed  to  implement  the  transformation  of electrolyzer combination and change the route of loading. A typical optimization example from an aluminum plant in northwest China is given in this paper, the results of which demonstrate the effectiveness of the proposed method.